Elemental mercury neurotoxicity and clinical recovery of function: A review of findings, and implications for occupational health - Calabrese, Edward J.; Iavicoli, Ivo; Calabrese, Vittorio; Cory-Slechta, Deborah A.; Giordano, James (Environmental research, 2018)
This paper assessed approximately 30 studies, mostly involving occupationally exposed subjects, concerning the extent to which those who developed elemental mercury (Hg)-induced central and/or peripheral neurotoxicities from chronic or acute exposures recover functionality and/or performance. While some recovery occurred in the vast majority of cases, the extent of such recoveries varied considerably by individual and endpoint. Factors accounting for the extensive inter-individual variation in toxicity and recovery were not specifically assessed such as age, gender, diet, environmental enrichment, chelation strategies and dose-rate. While the data indicate that psychomotor endpoints often show substantial and relatively rapid (i.e., 2–6 months) recovery and that neuropsychological endpoints display slower and less complete recovery, generalizations are difficult due to highly variable study designs, use of different endpoints measured between studies, different Hg exposures based on blood/urine concentrations and Hg dose-rates, the poor capacity for replicating findings due to the unpredictable/episodic nature of harmful exposures to elemental Hg, and the inconsistency of the initiation of studies after induced toxicities and the differing periods of follow up during recovery periods. Finally, there is strikingly limited animal model literature on the topic of recovery/reversibility of elemental Hg toxicity, a factor which significantly contributes to the overall marked uncertainties for predicting the rate and magnitude of recovery and the factors that affect it. Mercury toxicity and clinical recovery: a dose-time relationship. [Display omitted] •Substantial human studies, both acute and chronic, are available for evaluation.•Elemental mercury induced toxicity often displays substantial recovery.•Numerous examples fail to show full recovery from elemental mercury toxicity.•Recovery from elemental mercury toxicity is affected by age and endpoint.•Few animal studies have been directed to elemental mercury toxicity recovery.